EXPLORING THE EFFECTS OF COLD-WATER SWIMMING ON OBESE POPULATION: A SYSTEMATIC REVIEW - Maria Theodorou; Russell Kabir (Journal of Applied Sports Sciences, 2019)
Background: Obesity is a life-threatening condition linked to various diseases in all ages. Most common interventions focus on physical activity though there are some drawbacks limiting peoples’ participation in exercise. Swimming targets these limitations offering promising results to people who wish to improve their lifestyle. Objectives: The aim of this review is it to investigate the effects cold water can have on the obese population. This will be done by examining the physiological effects of swimming, understanding if different water temperatures can result in different outcomes and finding any other benefits that come along with swimming exercise. Search Strategy: PubMed, EbscoHost and Google Scholar are used as search engines to find the appropriate papers using the words obese, overweight, swim, aquatics, water immersion. A systematic review summarises the findings of primary research papers. This review is based according to the PICO guidelines and all the selected papers are evaluated using the CASP tool. A meta-synthesis summarises the results of the papers. Results: Results indicated that swimming helps people lose weight while providing additional benefits such as decreasing joint pain in people suffering from osteoarthritis. Furthermore, positive results are seen in anthropometric measures, physiological responses, and body composition. Conclusions: It is concluded that water-based exercise can prove an effective intervention for obese people wishing to lose weight. Results were seen from different protocols and water temperature was difficult to monitor. Future research should use the same exercise design in various water temperatures to fully understand the differences in the results.